2020
DOI: 10.2147/opth.s282059
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role and Significance of Ocular Demodicosis in Patients with Concomitant Refractory Herpetic Keratitis

Abstract: Purpose To evaluate the role of Demodex infestation of the eyelids in patients with recurrent herpetic keratitis. Patients and Methods This is a retrospective and noncomparative case series. Twenty-seven patients with ocular demodicosis and recurrent herpetic keratitis under conventional treatments were enrolled. Demographic data and clinical photographs were collected. Ocular demodicosis was confirmed by eyelash examination under a microscope. Eyelid scrub was initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Differential diagnosis of inflammatory conditions, especially in the anterior compartment of the eye, is essential [ 8 ]. When diagnosing infectious agents such as Herpes virus, Demodex leads to misdiagnosis as viral keratitis or allergic conjunctivitis [ 19 ]. In cases of recurrent viral keratitis, comorbid ocular demodicosis should be considered to prevent the viral infection from entering the cornea [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis of inflammatory conditions, especially in the anterior compartment of the eye, is essential [ 8 ]. When diagnosing infectious agents such as Herpes virus, Demodex leads to misdiagnosis as viral keratitis or allergic conjunctivitis [ 19 ]. In cases of recurrent viral keratitis, comorbid ocular demodicosis should be considered to prevent the viral infection from entering the cornea [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in patients with demodicosis, the combination of anti-degenerative and antibacterial therapy often gave better results [ 39 ]. Moreover, it is indicated based on the clinical observations of Hung et al, 2021 [ 40 ] on coexisting infestation with Demodex sp. infestation in patients with herpetic keratitis [ 40 ].…”
Section: Demodicosis Etiology and Coinfectionsmentioning
confidence: 99%
“…Moreover, it is indicated based on the clinical observations of Hung et al, 2021 [ 40 ] on coexisting infestation with Demodex sp. infestation in patients with herpetic keratitis [ 40 ]. Due to the possibility of transmitting pathogenic microorganisms, inflammatory reactions may develop even after the elimination of demodicosis.…”
Section: Demodicosis Etiology and Coinfectionsmentioning
confidence: 99%
“…Although this report elaborates a role for acarians in the pathophysiology of AD, other diseases associated with IgE likely also involve acarians. Demodex have been implicated in the pathophysiology of recurrent herpetic keratitis [ 104 ]. Persons with recurrent herpetic keratitis present with cylindrical dandruff [ 105 ], a finding pathognomonic of demodicosis.…”
Section: Connecting Dotsmentioning
confidence: 99%
“…Persons with recurrent herpetic keratitis present with cylindrical dandruff [ 105 ], a finding pathognomonic of demodicosis. Importantly, treatment of ocular demodicosis resolves the keratitis [ 104 ]. Of note, persons suffering from recurrent herpetic infection have elevated IgE at the time of exacerbation [ 106 ].…”
Section: Connecting Dotsmentioning
confidence: 99%